Synergistic Effect of Sadyovamana and Virechana in Udarda (AYUSHDHARA, 2025)
Udarda, a condition akin to urticaria, is an acute hypersensitivity reaction characterized by erythematous rashes, pruritis, edema primarily caused due to the vitiation of Pitta, Kapha and Vata dosha. Urticaria refers to transient redness and swelling of skin associated with itching, wheals or large hypodermal swellings. Materials and methods: A female patient aged 14 years presented with erythematous papules associated with itching and burning sensation over the lesions since 3 years was diagnosed as Udarda. The patient was treated with Sadyovamana followed by Kramataha Virechana and oral medications. Results: Post treatment, the patient exhibited significant reduction in itching, rashes and swelling, with overall wellbeing preventing further relapses during follow up period. Conclusion: Conventional management provides symptomatic relief but often fails to address underlying pathophysiology, leading to recurrent episodes. Panchakarma offers a holistic approach to detoxification and Dosha balance, thereby preventing recurrence.